(untitled) (CIPEEX, 2025)
ABSTRACT This paper aims to develop a predictive analytics platform for strategic management of football teams, integrating financial analysis of clubs and player performance. The goal is to assist in strategic decision-making to enhance management and sports outcomes, utilizing Descriptive Analysis, quantitative and qualitative data analysis, and soon predictive analysis using statistical or machine learning models to forecast future financial transactions based on historical data. The platform is divided into modules focused on the financial health of the clubs and the performance of the players. The work emphasizes the importance of management that balances financial and performance aspects, arguing that such an approach can lead to superior team performance. Preliminary results suggest that the platform can provide valuable insights for more informed management, offering a competitive edge in the sports landscape. Keywords: Predictive analysis, strategic management, football, financial health, player performance, decision-making.